Morphology-controlled one-dimensional ZnO nanostructures with customized Ga-doping - Song, Yong-Won; Lee, Sang Yeol (ELSEVIER SCIENCE SA, 2009)
Enhanced functionality of the nanostructure-based devices can be achieved by customizing the doping, thereby managing the electrical properties of the nanostructures. We have optimized the synthesis condition of the ZnO nanowires (NWs) using hot-walled pulsed laser deposition (HW-PLD) that features the facilitated kinetic energy control of the laser-ablated particles. The electrical properties of the NWs have been managed by doping control while maintaining the NW morphologies. 1, 3, and 5 wt.% Ga concentration in the NWs is evaluated directly with energy dispersive spectrometer (EDS), and the exciton peak shifts are measured with room temperature photoluminescence (PL) to find the correlation between the concentration and the shifts. n-type Ga-doping status has been verified with low temperature PL to find the donor-bound exciton peaks. As for the morphology diversification, we have acquired both zigzag-shaped NWs and nanohorns using the same HW-PLD. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: PULSED-LASER DEPOSITION; NANOWIRES